2013
DOI: 10.1007/s11524-013-9819-6
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Pregnancy in Adolescents: Association with Family Structure, Employed Mother, and Female Friends with Health-Risk Habits and Behaviors

Abstract: Previous publications have suggested that living in a nonintact family household and socializing with girlfriends who smoke or who consume alcoholic beverages favor the development of health-risk habits and customs in adolescents. However, their relationship with unplanned pregnancy in adolescents has not been determined. We investigated the association between family structure, employed mother, and female friends with health-risk habits and behaviors with unplanned pregnancy in adolescents (n = 3,130). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
1
11
0
6
Order By: Relevance
“…In addition, women who reported three or more pregnancies had higher odds of experiencing unplanned pregnancy than did those who had one or two pregnancies (adjusted OR = 2.26, 95% CI: 1.66–3.08). These results were consistent with those from previous research [ 48 50 ]. For example, a study conducted in Ethiopia revealed that a higher number of pregnancies was associated with a greater chance of a woman experiencing an unplanned pregnancy (adjusted OR = 3.16, 95% CI: 1.37–7.30) [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, women who reported three or more pregnancies had higher odds of experiencing unplanned pregnancy than did those who had one or two pregnancies (adjusted OR = 2.26, 95% CI: 1.66–3.08). These results were consistent with those from previous research [ 48 50 ]. For example, a study conducted in Ethiopia revealed that a higher number of pregnancies was associated with a greater chance of a woman experiencing an unplanned pregnancy (adjusted OR = 3.16, 95% CI: 1.37–7.30) [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…Studies by Ameyaw [25] and Nyarko [26] also found a negative relationship between age and unintended pregnancy. The finding that young women are at higher risk of unintended pregnancies has been explained in previous studies by Vázquez-Nava et al [32], Christofides et al [33] and Grindlay et al [27]. They explained that inadequate access to and use of contraceptives, risky sexual behaviour (increasing number of sexual partners and younger age at sexual debut) are the possible pathways through which young women risk unintended pregnancies.…”
Section: Discussionmentioning
confidence: 83%
“…6,7 Efforts to give lessons reproductive health or sex education to elementary school age children today is still considered taboo, so we must anticipate as soon as possible. To decrease maternal mortality rate and unmet need needs innovation to educate students.…”
Section: Introductionmentioning
confidence: 99%